A structured approach to a diagnostic of collective practices - Bicchieri, Cristina; Lindemans, Jan W.; Jiang, Ting (Frontiers in Psychology, 2014)
“How social norms change” is not only a theoretical question but also an empirical one. Many organizations have implemented programs to abandon harmful social norms. These programs are standardly monitored and evaluated with a set of empirical tools. While monitoring and evaluation (M&E) of changes in objective outcomes and behaviors is well developed, we will argue that M&E of changes in the wide range of beliefs and preferences important to social norms is still problematic. In this paper, we first present a theoretical framework and then show how it should guide social norms measurement. As a case study, we focus on the harmful practice of child marriage. We show how an operational theory of social norms can guide the design of surveys, experiments and vignettes. We use examples from existing research to illustrate how to study social norms change.